2003
DOI: 10.3171/foc.2003.15.5.6
|View full text |Cite
|
Sign up to set email alerts
|

En bloc spondylectomy for spinal metastases: a review of techniques

Abstract: Object Spinal metastases are prevalent in the population of patients with cancer. Effective cancer therapy must incorporate treatment strategies for these lesions. Increasingly, surgery is being recognized as an effective treatment modality both for the patient's quality of life and potential oncological cure. En bloc spondylectomy is the surgical procedure of choice to obtain these goals. The purpose of this study was to examine critically the rationale, indications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 22 publications
(30 reference statements)
1
35
0
2
Order By: Relevance
“…However, the indication of TES for spinal metastasis still remained controversial [18,19]. Interestingly, there were more cases with metastasis underwent TES than that with primary tumors in literature [1,2,4,5,8,17,18,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the indication of TES for spinal metastasis still remained controversial [18,19]. Interestingly, there were more cases with metastasis underwent TES than that with primary tumors in literature [1,2,4,5,8,17,18,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The previously described techniques were modified [7,32,37,58,59], prognostic surgical scores [56,57,60,61] were established considering the underlying tumor biology, the number/presence of extraspinal metastases and an estimation of life expectancy. With the results of these scores and the tremendous advance in spine surgery technique the indication from primary spinal tumors is now extended to selected cases of solitary spinal metastases with biologically favorable tumor entities [1,54,62,70]. Thanks to advances in tumor screening and diagnostics, the number of patients who may benefit from this extensive surgical treatment continues to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to advances in tumor screening and diagnostics, the number of patients who may benefit from this extensive surgical treatment continues to increase. Various authors have shown that en bloc spondylectomy, combined with multimodal therapies, can effectively reduce local recurrency rates and markedly prolong overall long-term survival [37,53,54,61,70]. However, to provide an acceptable patient outcome and quality of life, the basic knowledge of short-and long-term postoperative implant stability is a mandatory tool to carry into surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation of these striking differences included less violation of the tumor border, minimized tumor cell contamination and decreased tumor tissue derived blood loss. Application of these principles on solitary spinal metastatic disease have reinforced the concept of aggressive surgical treatment in selected patients, with biologically favorable cancers, who have the potential of long-term survival [3,28,39]. Despite conclusive evidence for significantly improved survival is missing to date, Sundaresan et al have shown that among 80 patients with solitary spinal metastases who underwent gross resection of tumor by various techniques, the rate of locoregional recurrences for the entire series was 32%, whereas only 17% of the patients who underwent en bloc resection experienced local recurrence [28].…”
Section: Discussionmentioning
confidence: 99%